Tete-A-Tete Project: software engineering tools supporting understanding - Hrytsay, V.P.; Zakhariya, L.M. (Проблеми програмування, 2012)
Software Understanding is necessary and the most important condition of essential reducing of software development cost. In this paper Tete-A-Tete Project is described which offers a radical rethinking of Software Development process and focuses on creating Understanding-Oriented Automated Software Engineering Tools. The project is based algebraic approach to the presentation of programs, which opens up the possibility of transformation and optimization programs. Implementation of the Tete-A-Tete Project will make it possible to build high quality software more quickly and with lower cost, than previously possible; will have essential impact on Software Reengineering and will lead to rethinking and reinvention of the Chief Programmer Team in the form of the Software Director Team. Познаваемость методов и средств разработки программного обеспечения является необходимым и наиболее важным условием существенного снижения стоимости программных систем. В этой работе описывается проект Tete-A-Tete, который предлагает радикальное переосмысление процесса разработки программного обеспечения и направлен на создание ориентированных на познаваемость автоматизированных средств разработки программных систем. В основе проекта лежит алгебраический подход к представлению программ, который открывает возможности трансформации и оптимизации программ. Реализация проекта Tete-A-Tete позволит создавать программное обеспечение более высокого качества , быстрее и с меньшими затратами, чем это было возможно ранее; окажет влияние на Реинжининг Программного Обеспечения и приведет к переосмыслению и возврату к использованию Бригады Главного Программиста в виде Бригады Программного Режиссера.